Nanoparticle-Based Immunoengineered Approaches for Combating HIV - Bowen, Allan; Sweeney, Elizabeth E.; Fernandes, Rohan (Frontiers in Immunology, 2020)
Highly active antiretroviral therapy (HAART) serves as an effective strategy to combat HIV infections by suppressing viral replication in patients with HIV/AIDS. However, HAART does not provide HIV/AIDS patients with a sterilizing or functional cure, and introduces several deleterious comorbidities. Moreover, the virus is able to persist within latent reservoirs, both undetected by the immune system and unaffected by HAART, increasing the risk of a viral rebound. The field of immunoengineering, which utilizes varied bioengineering approaches to interact with the immune system and potentiate its therapeutic effects against HIV, is being increasingly investigated in HIV cure research. In particular, nanoparticle-based immunoengineered approaches are especially attractive because they offer advantages including the improved delivery and functionality of classical HIV drugs such as antiretrovirals and experimental drugs such as latency-reversing agents (LRAs), among others. Here, we present and discuss the current state of the field in nanoparticle-based immunoengineering approaches for an HIV cure. Specifically, we discuss nanoparticle-based methods for improving HAART as well as latency reversal, developing vaccines, targeting viral fusion, enhancing gene editing approaches, improving adoptively transferred immune-cell mediated reservoir clearance, and other therapeutic and prevention approaches. Although nanoparticle-based immunoengineered approaches are currently at the stage of preclinical testing, the promising findings obtained in these studies demonstrate the potential of this emerging field for developing an HIV cure.